Internalisasi Nilai Pendidikan Karakter Berbasis Budaya Talaqqi di Pondok Pesantren Nurul Hakim Kediri Lombok Barat - Bustanul Arifin; Irsan Habsyi; Irwan Irwan (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Education is an effort to change behavior to be better than before, behavior change for students does not only cover the learning material provided, but instilling the character values of students requires strategies, behavior modification as a model that can be internalized and applied so that it becomes a permanent attitude as the main characteristic a student. The problem of this research: Character education which is proclaimed is a program that has no pattern, the research question is how is the internalization of the value of character education based on talaqqi culture in Islamic boarding schools? This study aims to describe the talaqqi strategy in implementing character education through the internalization of the moral values of the Islamic boarding school culture in Nurul Hakim, Kediri, West Lombok. The research approach is qualitative and the type of research is descriptive. Retrieval of data using non-participant observation techniques, in-depth interviews, and documentation, inductive data analysis. Validity test with credibility, dependability, confirmability, and discussion with peers. The results of the study show that the formation of the character of the students is carried out simultaneously by the teacher, environmental support, ustadz, and the culture of the Islamic boarding school. The character of the santri is formulated in the form of the Five Souls of Islamic Boarding Schools or the five souls of Islamic boarding schools which consist of a soul of sincerity, a spirit of Islamic ukhuwah, a spirit of independence, a spirit of simplicity, and a spirit of limited freedom. The instilled characters can be seen from the attitude of the students when they are inside and outside the Islamic boarding school environment. This research contributes to strengthening the elements of fostering character education through habituation carried out by educators by setting a noble example in the Islamic boarding school environment.